PENGARUH PELATIHAN LARI INTERVAL DENGAN RASIO KERJA DAN ISTIRAHAT 1:1 DAN 1:2 TERHADAP DAYA TAHAN KARDIOVASKULER - Januar Adiputra, Aendrik (Jurnal Ilmu Keolahragaan Undiksha, 2013)
This study was aimed to identify the effect of interval running training with work ratio and recovery 1:1 and 1:2 toward the cardiovascular endurance. This study was an experimental study which was designed in the randomized pretest-posttest control group design. There were 36 samples for this study which were decided by simple random sampling technique. Cardiovascular endurance measured by MFT test. From the result of independent sample t-test toward the cardiovascular endurance, there was obtained the score of tmeasure was 10.837 and 5.569 with significance 0.000. The significance was < 0.05, meant that there was different effect from each group. Then an anova test was conducted. The result of anova test showed that the variable of cardiovascular endurance between the experimental group and control group obtained Fmeasure of 65.737 and significance 0.000. Because there was a different effect, so the researcher conducted Least Significant Different (LSD) test in order to determine which training have better effect toward the improvement of cardiovascular endurance. Could be concluded that interval running training with work ratio and recovery 1:1 and 1:2 was affecting improvement of the cardiovascular endurance, in which interval running training with work ratio and recovery 1:1 have better effect for the improvement of cardiovascular endurance. From this study it is recommended that this study can be used as reference in conducting the next training and study.